Penerapan Model Cooperative Learning Tipe Jigsaw Dalam Pembelajaran Bahasa Arab - Shodiqul Bahroyni; Lutfi Kusuma Wardani (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2025)
This research stems from the problem of low student engagement and communicative skills in Arabic language learning, which is still dominated by a teacher-centered approach. The purpose of this study was to examine the implementation of the Jigsaw cooperative learning model in Arabic language learning for tenth graders at MA Al-Hidayat Ginuk Karas Magetan and to identify its strengths and challenges. The study used a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The results showed that the Jigsaw model was able to increase student participation, foster cooperation among students, and strengthen self-confidence in Arabic language learning. However, challenges were identified, including unequal roles within groups and limited discussion time. Overall, the Jigsaw model made a positive contribution to creating more active and participatory Arabic language learning.